Blended learning: benefits and disadvantages - Nazarova Dilshodakhon Ochildinovna (Zien Journals, 2023)
The current article aims at providing general information about blended learning, in comparison with both traditional and e-learning, and the dimensions that must be considered in order to create the best blend. The review shows that blended learning is not a new concept, but that it exists in many different forms and is prevalent in most classroom practices. The article also discusses benefits and disadvantages of blended learning
Keywords: blended learning; education program; hybrid learning; approach